Dynamics of Progressive Law Implementation in Indonesia: Prospects and Challenges of Law in the Era of Industrial Society 4.0 - Tanlim, Kiki; Nita, Surya; Badry, Ahmad Ibrahim Badry (Faculty of Law, Universitas Pekalongan, 2024)
This article aims to analyse the dynamics of progressive law implementation in Indonesia, as well as explore the various prospects and challenges facing the law in the Era of Industrial Society 4.0. The method used in this research is a literature review of publications in leading journals. Through literature analysis, this article identifies several factors that affect the implementation of progressive law in Indonesia, especially in the era of Industrial Society 4.0. First, there are challenges in terms of understanding and awareness of the concept and implementation of progressive law among legal practitioners and the general public. This limited knowledge and understanding can hinder the application of progressive law in everyday legal practice. Second, institutional factors also play an important role in the implementation of progressive law. Lack of government consistency along with commitment from legal institutions, such as the courts and the police, can hinder the implementation of progressive law. In addition, other challenges such as weaknesses in the judicial system and its bureaucracy, potential conflicts in values and culture, and imbalances in regulation can also be obstacles to the implementation of progressive law. This article also identifies the future prospects of progressive law implementation in Indonesia. With a growing awareness of the importance of progressive law in achieving social justice, there is potential for positive change. With growing awareness of the importance of progressive law in achieving social justice, there is potential for positive change. Improved legal education, training, and public awareness can strengthen the implementation of progressive law in Indonesia. Overall, this article concludes that the implementation of progressive law in Indonesia faces significant challenges, but also has bright prospects for the future. Collaborative efforts from various parties, including legal practitioners, legal institutions, and the general public, are needed to strengthen the implementation of progressive law and achieve better social justice in Indonesia.